Impact of the alkaline volatile trimethylamine on the physiology of Streptomyces venezuelae: an integrated transcriptomic and metabolomics study - Yanping Zhu; Hanlei Zhang; Meng Liu; Xiuhua Pang (Microbiology Spectrum)
ABSTRACT Streptomyces bacteria use volatile compounds for a range of functions, including communication and to kill competing species. We previously showed that the wild-type Streptomyces venezuelae strain ISP5230 produces the alkaline volatile trimethylamine (TMA), which can completely rescue the morphological defects of the S. venezuelae mutant strain MU-1, suggesting that TMA can have a significant impact on Streptomyces physiology. In this study, we further characterized strain MU-1 and elucidated the effects of alkaline volatiles on S. venezuelae by comparing the transcriptomic data of the wild-type strain ISP5230 and strain MU-1. Our RNA-sequence analysis revealed that MU-1 exhibited differentially expressed genes (DEGs) in multiple categories, including genes involved in development, carbon metabolism, antibiotic production, and transport, and these data were verified by real-time PCR analysis. Using metabolomics analysis, we next showed that organic acids accumulated in MU-1, consistent with the acidification of the growth medium by MU-1. In addition, our quantitative analysis showed much higher residual glucose content in the growth medium of MU-1, suggesting inefficient consumption of glucose by this mutant. Notably, TMA exposure restored the normal expression pattern of the DEGs in MU-1, consistent with the ability of TMA to rescue the MU-1 phenotype, including morphology, acidification of the growth medium, glucose uptake, and antibiotic production; these findings indicated a global impact of TMA on S. venezuelae physiology. In conclusion, our study suggests that the alkaline volatile TMA profoundly affects the physiology of S. venezuelae and may promote the growth of S. venezuelae mutants, enabling their survival in complex microbial communities.IMPORTANCEMicrobes produce a wide array of volatile compounds for which diverse biological roles have been implicated in microbial volatiles. In Streptomyces, the alkaline volatile trimethylamine (TMA) enables communication between cells, and in Streptomyces venezuelae, TMA could also rescue the defective morphology of the mutant strain MU-1, indicating a broader impact of TMA on Streptomyces physiology. In this study, we identified differentially expressed genes (DEGs) in MU-1 and demonstrated that TMA exposure induced normal expression of these DEGs in the mutant strain to levels comparable with those in the wild-type strain, consistent with the ability of TMA to rescue the abnormal phenotype of this mutant. Our study expands the role of TMA to a global impact on the physiology of recipient cells and adds a new understanding of the importance of volatile compounds in microbial communities.